Craniofacial catch-up growth in intrauterine growth retarded rats following postnatal nutritional rehabilitation - Luna, Maria Eugenia (2014)
Purpose: The aim of the study was to analyze the effect of postnatal nutritional rehabilitation on the craniofacial growth in rats with intrauterine growth retardation (IUGR). Materials and Methods: Wistar rats were assigned to one of the following groups: control, Sham-operated, and IUGR. The IUGR was produced by uterine vessels bending (day 14 of pregnancy). At days 1, 21, 42, 63, and 84 of postnatal life, each animal was X-rayed, and neural and facial length, width and height were measured. Volumetric and morphometric indices were calculated. Results: The decreased maternal-fetal blood flow during the last-third of the gestation period modified cranial size and shape of both sexes at birth. Discussion: Postnatal nutritional rehabilitation is not fully sufficient to reverse the prenatal growth retardation. There are specific responses depending on the sex and the age of the IUGR pups. Regardless of the changes in size, the shape is not modified during all the postnatal period.